Unusual Complication of Multidrug Resistant Tuberculosis - Prerna Sharma; Ravindra Nath Sahay (Case Reports in Nephrology)
Introduction. Capreomycin is a second-line drug often used for multidrug-resistant tuberculosis which can result in nephrotoxic effects similar to other aminoglycosides. We describe a case of capreomycin induced Bartter-like syndrome with hypocalcemic tetany. Case Report. 23-year-old female patient presented with carpopedal spasms and tingling sensations in hands. Patient was being treated with capreomycin for two months for tuberculosis. On further investigation, hypocalcemia, hyponatremia, hypomagnesemia, hypokalemia, and hypochloremic metabolic alkalosis were noted. Vitamin D and serum PTH levels were within normal limits. Hypercalciuria was confirmed by urine calcium/creatinine ratio. Calcium, potassium, and magnesium supplementation was given and capreomycin was discontinued. Electrolytes normalized in two days after cessation of capreomycin with no further abnormalities on repeat investigations. Discussion. Aminoglycosides can result in renal tubular dysfunction leading to Fanconi syndrome, Bartter syndrome, and distal tubular acidosis. Impaired mitochondrial function in the tubular cells has been hypothesized as the possible cause of these tubulopathies. Acquired Bartter-like syndrome phenotypically resembles autosomal dominant type 5 Bartter syndrome. Treatment consists of correction of electrolyte abnormalities, indomethacin, and potassium-sparing diuretics. Prompt diagnosis and treatment of severe dyselectrolytemia are warranted in patients on aminoglycoside therapy.